Analysis of Rhodamin B on Lipstick, Blush On and Eye Shadow in Pekalongan Regency With Uv-Vis Spectrophotometer - Rahmasari, Khusna Santika; Waznah, Urmatul (Universitas Muhammadiyah Kalimantan Timur, 2022)
Rhodamine B is a synthetic dye that is often misused in cosmetic products. These dyes can cause irritation to the respiratory tract, are carcinogenic and cause liver damage in high concentrations. This study aims to determine the content of rhodamine B in lipstick, blush on, and eye shadow in the Pekalongan Regency. The analysis used in this research is qualitative and quantitative analysis. Qualitative study using Thin Layer Chromatography (TLC) with silica gel F254 as stationary phase and mobile phase n-butanol, ethyl acetate, ammonia (5.5 : 2: 2.5) and then detected on UV lamps at 254 nm and 366 nm. Quantitative analysis using UV-Vis spectrophotometer at a maximum wavelength of 557 nm. The results of the qualitative analysis showed that three samples of lipstick (sample A, D and E), two samples of blush on (sample B and C), and three samples of eye shadow (sample A, B and E) contained rhodamine B. Rhodamine B levels in the sample lipstick A 0.00244%, lipstick D 0.00052%, lipstick E 0.00065%, blush on B 0.00239, blush on C 0.01091%, eye shadow A 0.00057%, eye shadow B 0.00140, and eye shadow E 0.00047%.